Penerapan Konsep “Welcome to Malang” Pada Desain Interior Perpustakaan Umum dan Arsip Kota Malang - Irene Nathania Japutra (Intra, 2014)
Public Library and Archive of Malang is a library that managed by the city government. The library financed by government for library development. The development of the library collection has been done and needs further development on its interior design. This development aims to fix the library interior in order to support the library system and make it more comfortable and interesting. The library is expected to become an icon of Malang’s education. This expectation then bodied in the library re-design theme, called "Welcome to Malang". “Welcome to Malang” expresses acceptance and friendliness. Under this concept, the culture of Malang will be revealed. Theme then divided into 3 sub-concepts, namely: "Batik Malangkucecwara" which was applied to interior elements and color scheme of the lobby, "Apple Plantation" which was applied to layout arrangement, furniture design, and decorative elements of children's library, and the "Society of Malang" shown in the public library area layout arrangement and material selection. The common thread of all three sub-concept is shown in the open plan layout arrangement and material selection.